2018
DOI: 10.1111/bjh.15656
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of long non‐coding RNAs are related to proliferation and histological diversity in follicular lymphomas

Abstract: Long non-coding RNAs (lncRNAs) comprise a family of non-coding transcripts that are emerging as relevant gene expression regulators of different processes, including tumour development. To determine the possible contribution of lncRNA to the pathogenesis of follicular lymphoma (FL) we performed RNA-sequencing at high depth sequencing in primary FL samples ranging from grade 1-3A to aggressive grade 3B variants using unpurified (n = 16) and purified (n = 12) tumour cell suspensions from nodal samples. FL grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…These results showed that RP4-694A7.2 is an oncogene that promotes HCC development and metastasis. Our results that RP4-694A7.2 is related to increased tumor cell proliferation was consistent with those of a previously published study 19 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results showed that RP4-694A7.2 is an oncogene that promotes HCC development and metastasis. Our results that RP4-694A7.2 is related to increased tumor cell proliferation was consistent with those of a previously published study 19 .…”
Section: Discussionsupporting
confidence: 94%
“…We found that RP4-694A7.2 expression is higher in HCC malignant tissues than in normal liver tissues. Recently, RP4-694A7.2 has been found in some solid cancers 14 , 19 ; however, its expression patterns and functions in HCC are still unknown. Our results suggested that RP4-694A7.2 is upregulated in HCC and might contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs), transcripts with longer than 200 nucleotides in length, have emerged as important regulators of disease processes including cancer [5]. Several lncRNAs have been shown to exhibit a potential role in lymphomagenesis [6,7]. Usually, lncRNAs will run their functions through complete regulatory correlations, such as by targeting genes, proteins, or miRNAs [5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing evidence has suggested that lncRNAs can participate in the regulation of various levels of chromosome modification, RNA transcription, and protein translation in physiological cell processes (Hon et al, 2017;Park et al, 2018;Podbevsek et al, 2018). In addition, lncRNAs can also have important effects on various stages of cell physiology (Misawa et al, 2016;Roisman et al, 2019;Xu et al, 2019). At the present time, a large amount of literature has shown that lncRNAs can regulate the development of bladder cancer in various ways.…”
Section: Discussionmentioning
confidence: 99%